Estimate pathomorphology of nano-selenium biology influence under the poisonous action to the hepart - E. A. Karpova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The result presents in the article of the morphological and histochemical studies of the liver on the model of experiment toxic hepatitis CCl4 on rats and this correction nanopreparation of selenium. It has been shown that the drag of nanoselenium in the arabinogalactan matrix has hepetoprotective property. This is manifests in the protective effect of hepatocyte damage from the toxic carbon tetrachloride. On the seventh day of experiment ascertained atomized fatty degeneration, it will has disappear by fourteenth day of experiment, then hepatocytes has monomorphic sizes and well-marked nucleus and evenly distributed chromatin. The activity of enzymes and glycogen preserves, the lipid content reduce. The nanocomposite preparation of selenium reduces poisonous action to hepatocytes.